Distribution and Anisotropy of the Energy Transfer Rate in the Solar Wind Turbulence - Wu, Honghong; Huang, Shiyong; Wang, Xin; Yang, Liping; Yuan, Zhigang (The Astrophysical journal, 2024)
The distribution of the energy transfer rate is critical for the interpretation of the intermittent energy cascade in the solar wind turbulence. However, the true observational distribution of the energy transfer rate in the solar wind and its anisotropy remain unknown. Here, we use a 7 day interval measured by Wind in the fast solar wind and investigate the distribution and anisotropy of the energy transfer rate based on the log-Poisson model. We find that the probability density distribution consists of two parts. The majority part locates at smaller values and is consistent with the log-normal distribution. The estimated mean value and standard deviation of the logarithmic energy transfer rate for the majority are both smaller in the direction parallel to the local mean magnetic field than in the perpendicular direction. The mean value displays a power-law shape with respect to the scale, with flatter index in the parallel direction and steeper index in the perpendicular direction. The minority part locates at larger values and expands as the scale decreases, indicating the growing intermittency toward smaller scales. The flatness for parallel logarithmic energy transfer rate is larger than that for perpendicular. And it rises as the scale decreases for all directions, demonstrating the relatively longer tail of the distribution with decreasing scale. Our results provide new insight to help interpret the intermittent energy cascade process in the solar wind turbulence.